2018
DOI: 10.21608/ejrs.2018.44315
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and Physiological Response of New Zealand White Rabbit Does Fed on Discarded Palm Fronds.

Abstract: This study carried out to determine the effects of substitution 25 and 50% of clover hay with discarded palm fronds (DPF) or biologically treated discarded palm fronds (Bio-DPF) in does diet on reproductive, physiological response and economic efficiency of New Zealand White (NZW) rabbit does. Twenty five New Zealand White (NZW) does aged 5 months weighting 3140± 26.55g were randomly distributed into 5 experimental treatments (5 does/ treatment). Experimental diets were as follows: diet 1: A control without su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…On contrary to this result, Ríos‐Rincón et al ( 2014 ) reported that rib eye muscle area was not significantly affected with different diet consisting of different proportion of protein and energy. El‐Banna, El‐Manylam, et al ( 2010 ) reported higher ADG (19.72 vs. 21.5 g/day), pre‐SW (1885 vs. 1968 g), DP (59.9% vs. 61.6%), and lower FCE (4.56 vs. 4) for rabbits fed on potato vines that were treated with L. acidophilus compared to rabbits fed untreated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On contrary to this result, Ríos‐Rincón et al ( 2014 ) reported that rib eye muscle area was not significantly affected with different diet consisting of different proportion of protein and energy. El‐Banna, El‐Manylam, et al ( 2010 ) reported higher ADG (19.72 vs. 21.5 g/day), pre‐SW (1885 vs. 1968 g), DP (59.9% vs. 61.6%), and lower FCE (4.56 vs. 4) for rabbits fed on potato vines that were treated with L. acidophilus compared to rabbits fed untreated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, growing animals fed on biologically treated roughages showed better daily gain (Allam et al, 2006), FCE, and pre-slaughter live weight (El-Marakby, 2003) compared to animals fed untreated roughages. In El-Banna, El-Manylam, et al (2010), higher average daily gain (ADG) (19.72 vs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation